2018
DOI: 10.2147/ceg.s153676
|View full text |Cite
|
Sign up to set email alerts
|

Colonic transit time and pressure based on Bernoulli’s principle

Abstract: PurposeVariations in the caliber of human large intestinal tract causes changes in pressure and the velocity of its contents, depending on flow volume, gravity, and density, which are all variables of Bernoulli’s principle. Therefore, it was hypothesized that constipation and diarrhea can occur due to changes in the colonic transit time (CTT), according to Bernoulli’s principle. In addition, it was hypothesized that high amplitude peristaltic contractions (HAPC), which are considered to be involved in defecati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 55 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Therefore, the use of a 10 mm instrument on the umbilical site does not negatively impact cosmetic outcomes. Furthermore, according to recent studies on the mechanism of bowel movement and its pathologies, it was shown that the normal pressure in the cecum is 60–80 mmHg, which decreases to 20–40 mmHg in the central part of the large bowel and then increases to 60–100 mmHg in the proximity of the rectum [ 44 , 45 , 46 , 47 , 48 ]. This finding supports our theory that a maximum burst resistance of 60.5 mmHg achieved with a 5 mm instrument is insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the use of a 10 mm instrument on the umbilical site does not negatively impact cosmetic outcomes. Furthermore, according to recent studies on the mechanism of bowel movement and its pathologies, it was shown that the normal pressure in the cecum is 60–80 mmHg, which decreases to 20–40 mmHg in the central part of the large bowel and then increases to 60–100 mmHg in the proximity of the rectum [ 44 , 45 , 46 , 47 , 48 ]. This finding supports our theory that a maximum burst resistance of 60.5 mmHg achieved with a 5 mm instrument is insufficient.…”
Section: Discussionmentioning
confidence: 99%